Brexit : sociological responses - Outhwaite, William (London, UK : Anthem Press, 2017)
This book aims to trace the implications of the UK's projected withdrawal from the EU, locating short-term political fluctuations in a broader historical and social context of the transformation of European and global society. It provides a forum for leading Eurosociologists (broadly defined), working inside and outside the UK, to rethink their analyses of the European project and its prospects, as well as to reflect on the likely implications for the UK.
The increasing inevitability of that referendum / Martin Westlake -- Vox Populi: nationalism, globalization and the balance of power in the making of Brexit / Jonathan Hearn -- Exit from the perspective of entry / John Holnwood -- Brexit, sovereignty and the end of an ever closer union / Stefan Auer -- Populism, nationalism and Brexit / Craig Calhoun -- A tale of two constitutions: whose legitimacy? Whose crisis? / Chris Thornhill -- Locating Brexit in the pragmatics of race, citizenship and empire / Gurminder K. Bhambra -- Globalization, nationalism, and the changing axes of political identity / Colin Crouch -- A divided nation in a divided Europe: emerging cleavages and the crisis of European integration / Gerard Delanty -- The EU and Brexit: processes, perspectives, and prospects / Tim Oliver -- The impossibility of disentangling integration / Antje Wiener -- No exit from Brexit? / Simon Susen -- Critical theory, Brexit and the vicissitudes of political economy in the twenty-first century / Harry F. Dahms -- European Union versus European society: sociologists on "Brexit" and the "failure" of europeanization / Adrian Fawell.
Includes bibliographical references and index.
Keywords: European Union -- Great Britain; European Union -- Membership; Referendum -- Great Britain -- History -- 21st century; Great Britain -- Relations -- European Union countries; European Union countries -- Relations -- Great Britain